PHYSIOLOGICAL INDICATORS OF CHICKENS BELONGING TO THE PROSPECTIVE LOHMANN BROWN-CLASSIC AND LOHMANN SANDY CROSSES IN THE CONDITIONS OF NORTHERN POLAND (Conferencea, 2023)
In this article, physiological indicators of chickens belonging to “Lohmann brown-classic” and “Lohmann sandy” crosses are studied, analyzed and conclusions are given.